ANALISIS DAN PERANCANGAN SISTEM INFORMASI PEMASARAN PERUMAHAN BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE PADA PT LESTARI INTI PROPERTI JAMBI: Marketing Information System, Web-Based Application, Prototype Method, Unified Modeling Language, Subsidized Housing - Alghifari, Hamzah; Akbar, Niko; Abdillah, Nurul; Dahwanu, Oki (JURNAL AKADEMIKA, 2025)
Due to its manual reliance on conventional promotional techniques such as distributing flyers and posters, PT Lestari Inti Properti faces challenges in selling subsidized housing products. In the digital era, this situation limits promotional reach and reduces marketing effectiveness. The goal of this project is to create a web-based marketing information system that can manage the company's sales and administration data in an integrated manner and function as a digital promotional tool. Using the Unified Modeling Language (UML) methodology, prototyping techniques are applied through the phases of rapid design, testing and feedback, prototyping, and requirements communication. The result of this study is the design of a prototype housing marketing information system that includes a login module, housing data management, ordering procedures, and transaction reports. Use case structures, activity diagrams, and class diagrams are used in the design of this system to fully explain how users interact with business operations. This system can increase marketing reach, speed up administrative procedures, and reduce data input errors, according to the design results. Therefore, PT Lestari Inti Properti can improve operational effectiveness and competitiveness in the digital market by using a web-based marketing information system.